Hubungan Ekspektasi Usaha Dan Ekspektasi Kinerja Dengan Efisiensi Pemanfaatan Sistem Informasi Manajemen Rumah Sakit Pada Instalasi Rawat Jalan Di RSUD Rantau Prapat Tahun 2024 - Akhmad Fatikhus Solikh; Monika Nina Kurniawaty Ginting; Andreas Lewis; Desmayanti Surbakti (BEST Journal (Biology Education, Sains and Technology), 2025)
Background: The purpose of the study is to determine the relationship between business expectations and the results and effectiveness of the use of the hospital management information system at Rantauprapat Hospital in 2024. The research method used is analytical and descriptive with a cross-sectional approach. Data were collected through questionnaires and analyzed using multiple linear regression. We hope that the results of this study can provide insight into hospital management in improving the effectiveness of the use of management information systems. This study uses an analytical descriptive approach with a cross-sectional method. Data was collected through a questionnaire filled out by respondents at Rantauprapat Hospital. Data analysis was carried out using multiple linear regression to test the relationship between business expectations, performance expectations, and the effectiveness of SIMRS utilization. This method is used to understand the impact of these variables on the use of hospital management information systems. The results of the study show that there is a relationship between business expectations and performance expectations on the effectiveness of SIMRS utilization at Rantauprapat Hospital. The results of the chi-square test obtained the value of Exact Fisher with Exact. Sig (2-sided) of 0.001 or smaller than (α0.005). Therefore, it can be concluded that H0 is rejected and H1 is accepted, which means that there is a relationship between business expectations and the efficiency of SIMRS utilization in the outpatient installation of Rantauprapat Hospital, Labuhanbatu Regency